"The spirit which dictates them" : Ralph Waldo Emerson?s Transcendental Decision to Decline the Social Reform of Brook Farm, 1840 - Furlong, Ryan D. (My University, 2014)
Ralph Waldo Emerson's decision to decline George Ripley's invitation to join the proto-socialist Brook Farm in December of 1840 has been a definitive event for understanding both Emerson's complex relationship to associationism and his reasons for abstaining from utopian ideology. Historians and critics have correctly pointed out the practical considerations Emerson faced with moving his family to the farm in West Roxbury, Massachusetts and stifling his literary work, while concurrently addressing his long-trumpeted notion of "self-reliance," in which individual reformation preceded societal transformation. What has been partially misunderstood, however, is the authoritative nature of Emerson's Transcendental theory in relation to Brook Farm. This paper attempts to re-clarify and establish this former point as an essential component to Emerson?s self-reliance and how it contributed to the rejection, proving to be an irreconcilable barrier to commit his residence, money, and intellectual support to Brook Farm in 1840.
Keywords: Emerson, Ralph Waldo, 1803-1882--Philosophy; Emerson, Ralph Waldo, 1803-1882--Political and social views; Brook Farm Phalanx (West Roxbury, Boston, Mass.); Transcendentalism (New England)--Social aspects; Utopias--United States--History--19th century